Honra e infâmia no cerrado: representações do coronelismo em Herança de Sangue de Ivan Sant’anna - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
This research intended to analyze the ways in which coronelismo, honor and infamy are represented in the novel Herança de Sangue: um faroeste brasileiro, published in 2012, from the contemporary author Ivan Sant’anna. For this purpose, we are guided methodologically by the bibliographic research regarding the relevant concepts to the research, using the theoretical contribution of scholars such as Leal (1997), Janotti (1992), Queiroz (1976) among others, who treats about coronelismo; Bosi (2015, 2017), Cândido (2006), among others, to address issues related to literary analysis, and Oliveira (2015, 2016a, 2016b), Rohden (2006) and Klein (2010), regarding issues related to honor and infamy. Thus, the final phase of the research had as methodology the articulation between the theory and the analysis of the novel. In Herança de Sangue, there is a reconstruction of a part of the history of Catalão in Goiás, showing the ways in which Catalan society was constituted under the aegis of bravery and the exaltation of violence. It is noticed that the coronelismo portrayed in the novel shows similarities with what was portrayed in other literary works, but it differs from these representations in that it removes the focus from the coronel-clientele relationship and focuses on the coronelismo-violence relationship. In addition, the limits between honor and infamy, just as they are blurred in society in general, are inter-relate in the context of the coronelismo of the narrative. In a growing movement, the violence exalted by Catalão, begins to betray the city, making it an infamous city, making the city and its inhabitants suffer with its consequences.
Honor and infamy in the cerrado: representations of coronelismo in Herança de Sangue by Ivan Sant’anna
Keywords: Coronel; Literatura goiana; Literatura goiana - Valentia; Literatura goiana - Covardia; Literatura goiana - Violência; Colonel; Literature of Goiás; Literature of Goiás - Bravery; Literature of Goiás - Cowardice; Literature of Goiás - Violence; LETRAS::LITERATURA BRASILEIRA